"Money, time and rationality in max weber" - "Parsons, Stephen D." (London, 2003)
This unique study into the roots of Max Weber's Political Economy, is an intriguing read and a valuable contribution to the Weberian literature. Parsons argues that Weber's analysis is highly influenced by the Austrian School of Economics and the relationship between his critique of centrally planned economies and that of Mises.
Keywords: Economics - Austria - history